Diffusion-weighted imaging and loco-regional N staging of patients with colorectal liver metastases. Issue 3 (March 2019) - Bonifacio, Cristiana; Viganò, Luca; Felisaz, Paolo; Lopci, Egesta; Cimino, Matteo; Poretti, Dario; Donadon, Matteo; Pedicini, Vittorio; Procopio, Fabio; Chiti, Arturo; Balzarini, Luca; Torzilli, Guido
Abstract: Introduction: Diffusion-weighted MRI (DWI) contributes to N staging of rectal cancers and diagnosis of colorectal liver metastases (CLM). About 15% of CLM patients have loco-regional lymph node (LN) metastases that impact prognosis and treatment strategy. This retrospective study is the first one to evaluate quantitative ADC measurement as a tool to identify metastatic LNs in patients with liver metastases from colorectal cancer. Methods: All consecutive patients undergoing surgery for CLM between 2008 and 2015 were considered. Inclusion criteria were: intraoperative retrieval of at least one LN; LN ≥ 5 mm; DWI performed ≤2 months before surgery. The ADC and ADCratio (ADCLN /ADCCLM ) were computed by two radiologists for all the LNs. Results: Among 555 patients operated for CLM, 32 met the inclusion criteria. Fifty-six LNs were analyzed and 28 were metastatic. ADC and ADCratio in metastatic LNs were lower than in benign LNs (ADC = 1.37 vs. 1.83 × 10 −3 mm 2 /s, p < 0.001; ADCratio = 1.26 vs. 1.73, p < 0.001). The optimal cut-off value for ADC was 1.48 x 10 -3 mm 2 /s (AUC = 0.85, p < 0.001, sensitivity/specificity/accuracy 79%/93%/86% in per LN-analysis and 94%/86%/91% in per-patient analysis). The optimal cut-off for ADCratio was 1.15 (AUC = 0.80, p < 0.001, sensitivity/specificity/accuracy 69%/93%/81% and 76%, 93%/84%). Excellent inter- and intra-operators' agreements were observed. Conclusion: In patients with CLM, ADC values < 1.48 x 10 -3 mm 2 /s can be postulated as a cut-off to distinguish metastatic LNs.